1996
DOI: 10.1243/pime_proc_1996_210_179_02
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Forced Convective Heat Transfer in Stationary and Rotating Annuli

Abstract: The study of heat transfer by forced convection in annular passages is of interest across the range of process and aeronautical industries, for examplefrom annular heat exchangers to the various configurations of annuli found in turbomachinery. The aim of this paper is to review relevant experimental, numerical and analytical research of heat transfer in both stationary and rotating annuli, with an emphasis on presenting useful information for designers. The geometries considered are the stationary annulus wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Figure 10 shows the average Nusselt number at different eccentricities for the three Reynolds numbers considered as well as for natural convection. In general, for a fixed Reynolds number, Nu decreased with increasing eccentricity, in conformity with the general conclusion of Childs and Long [10]. At low eccentricities (0 < e < 0.4), Nu was quite insensitive to e, however, at high eccentricities (0.8 <e< 0.9) Nu dropped to values that were roughly 60% lower than that in the concentric case.…”
Section: On the Significance Of Buoyancysupporting
confidence: 87%
“…Figure 10 shows the average Nusselt number at different eccentricities for the three Reynolds numbers considered as well as for natural convection. In general, for a fixed Reynolds number, Nu decreased with increasing eccentricity, in conformity with the general conclusion of Childs and Long [10]. At low eccentricities (0 < e < 0.4), Nu was quite insensitive to e, however, at high eccentricities (0.8 <e< 0.9) Nu dropped to values that were roughly 60% lower than that in the concentric case.…”
Section: On the Significance Of Buoyancysupporting
confidence: 87%
“…(10) in their work), but again there is a small difference; the constant Γ 3 in their work ( (Π−β) 2 Π 2 −1 , see paragraph below Eq. (8) in [14]) is not equal to ( Π(Π−β) Π 2 −1 ) 2 of this work, as it can be seen on the right-hand side of Eq.…”
Section: First Law Analysismentioning
confidence: 95%
“…Eckert number, = (r i ω i ) 2 The concepts of entropy generation number and irreversibility distribution ratio were introduced by Bejan [9], a considerable number of research studies were carried out to examine entropy generation in the flow systems with different geometric configurations, flow situations, and thermal boundary conditions. Bejan [9] obtained the entropy generation in fundamental convective heat transfer problems and provided some examples.…”
Section: Bementioning
confidence: 99%
“…The resulting graph is interesting because it shows the influence of a parameter that generally has no effect on the Nusselt number. Indeed, in many works [8][9][10][11] the solids constitute a uniform heat source, their conductivity having no effect. In the present case, the distribution of heat transferred from the solids to the fluid depends on the conductivity of the solids because of the localized heat source.…”
Section: Global Nusselt Numbermentioning
confidence: 99%
“…He proposed the use of the formulas obtained by Tachibana et al [8] and Gazley [9] in the study of heat transfer in an annulus between an inner rotating cylinder and an outer stationary one. A complete review of heat transfer in this type of flow can be found in [10]. On the other hand, Lebeck [1] suggested that the more useful correlation was that of Becker [11], deriving from experiments on a small diameter cylinder rotating in a tank of water.…”
Section: Introductionmentioning
confidence: 99%